Genetic Diversity and Demographic History in the Cactophilic Drosophila repleta Species Group (Diptera: Drosophilidae) in North America Inferred from Mitochondrial DNA Barcodes. (21st May 2018) - Pfeiler, Edward
Abstract: Genetic diversity in mitochondrial DNA barcodes, comprising a segment of the cytochrome c oxidase subunit I (COI) gene, was used to infer demographic histories in selected taxa of the cactophilic Drosophila repleta species group in North America. Haplotype and nucleotide diversities were determined in 16 taxa based on both previously published and new sequences. Haplotype diversity ( h ) differed dramatically in different taxa, varying from h = 0 in Drosophila eremophila, Drosophila hexastigma, and Drosophila bifurca to h = 0.99 in Drosophila hamatofila . Genetic diversity indices and sample sizes were sufficient to infer demographic histories from mismatch distribution analysis and Bayesian skyline plots for 9 taxa: Drosophila mojavensis baja, Drosophila mojavensis sonorensis, Drosophila arizonae, Drosophila aldrichi, D. hamatofila, Drosophila spenceri, Drosophila mainlandi, Drosophila mettleri, and Drosophila nigrospiracula . Evidence was found for both population expansions and relatively stable populations in these species. Demographic history varied dramatically in subspecies of D. mojavensis, showing a relatively stable population size over time in D. m. sonorensis from the mainland Sonoran Desert whereas a large population expansion was evident in D. m. baja from the Baja California Peninsula, providing support for the hypothesis that the split of sister species D. mojavensis and D. arizonae from a common ancestor occurred on the mainland rather than the peninsula as proposed by others. No evidence was found for a causal relationship between a stable or expanding population and host plant shifts from prickly-pear cactus to columnar cacti, which has occurred independently in many taxa of the repleta group.